Phosphorus use efficiency of different varieties of Lentil and grass pea - Hasan, Ahmed Khairul; Ashiquzzaman, Md; Quadir, Quazi Forhad; Ahmed, Istiaq (Research in Agriculture Livestock and Fisheries, 2015)
A pot experiment was conducted in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh during the period from October, 2012 to April, 2013 to compare the phosphorus use efficiency (PUE) as well as the effect of phosphorus (P) on yield and quality of six varieties of lentil and grass pea (three from each crop). The experiment was laid out in a Completely Randomized Design (CRD) with two treatments and three replications. Treatments included optimum phosphorus (P) dose i.e. @ 25 kg P ha-1 (P1) and control (P0). Among the observed parameters, application of P fertilizer had performed better over control (P0) in all varieties of lentil and grass pea. Among the three varieties of lentil (viz. BARI masur-5, BARI masur-6 and BARI masur-7), the best yield performance was observed in BARI masur-5. Similarly, among the three varieties of grass pea, (viz. BINA khesari-1, BARI khesari-1 and BARI khesari-2), BINA khesari-1 showed the best yield performance. In lentil varieties, BARI Masur-5 produced the highest seed yield (2.78 g pot-1), whereas, BINA kheshari-1 gave the highest yield (3.38 g pot-1) among grass pea varieties. In case of lentil and grass pea varieties, highest seed P contents were observed in BARI masur-5 (1.36%) and BINA khesari-1 (1.22%) varieties, respectively. Maximum PUE (192.5%) for lentil varieties was found in BARI masur-5 and that of (234.0%) for grass pea varieties was in BINA khesari-1. On the other hand, P used per unit seed yield in lentil and grass pea was highest in BARI masur-5 and BINA khesari-1, respectively. Therefore, our farmer can be benefitted by cultivating BARI masur-5 and BINA khesari-1 through maximized yield using less amount of P fertilizers. Res. Agric., Livest. Fish.2(2): 271-277, August 2015